Analisis Of Business Enlargement Gold Fish (Cyprinus carpio) Floating Cages In Sarasah Tanggo Kenagarian Sarilamak Sub Districts Harau District Lima Puluh Kota Province West Sumatra - Mardi Yanto; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted on January 25 to Ferbruay 10, 2016. This study aims to determine the total investment, the feasibility of aspects and problems faced by farmes in the enlarged business goldfish (Cyprinus carpio) in floating net cages in Nagari Sarasah Tanggo. The method used in this study is a survey with 9 respondents. Result of research show the total capital invested by farmers goldfish in floating cages an average Rp 81.695.733. The Benefits get an average Rp 24.975.044. With BCR value of 1,46 , FRR value 30,79%. PPC value of 3 period. The increasing of fish consumption every year fastly increase equal to 9,41%/year, so that there are opportunity of is effort to increase produce conducting Fishery. Water of Lake of Sarasah Tanggo up to standrt for the magnification of goldfish. Effort give positive impact to society that is can permeate of new labour. Keyword : Nagari Sarasah Tanggo, Investment, BCR, FRR, PPC, Cyrinus carpio